Preparation method of pure-phase sodium ion battery positive electrode material
By mixing sodium carbonate and citric acid and mixing with other raw materials, drying and sintering, a pure phase sodium ferro pyrophosphate positive electrode material was successfully prepared, which solved the poor performance problems caused by the miscellaneous phases in the prior art, and improved the circulation stability and electrochemical properties of the material.
Patent Information
- Application Number
- CN202411755833.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The prior art has a heterophase NaFePO4 when preparing the positive electrode material of sodium ferric pyrophosphate, resulting in poor material performance and sodium carbonate is prone to decomposition of gases in the ball mill mixing, which is highly risky.
The pure phase sodium ferric pyrophosphate was obtained by mixing sodium carbonate with a specific carbon source citric acid and combining with a specific mixing step. The specific steps include reacting sodium carbonate and citric acid in a solvent to obtain a first slurry, then mixing with iron phosphate, sodium dihydrogen phosphate and dispersant, drying to obtain a precursor, and then pre-sintering and sintering in a protective atmosphere.
The preparation of pure phase sodium ferric pyrophosphate is achieved, and the specific capacity of the material is closer to the theoretical specific capacity and has better cycle stability. The use of dispersant limits the growth of precursor particles, improves the conductivity and electrochemical properties of the cathode material, and reduces production costs.
Smart Images

Figure CN119560539A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials, and more specifically, to a method for preparing a pure-phase sodium ion battery positive electrode material. Background Art
[0002] Sodium-ion batteries are considered to be the most promising alternative to lithium-ion batteries due to their abundant sodium resources, low cost and high safety performance. In recent years, great efforts have been made to develop key technologies such as positive electrode materials, negative electrode materials and electrolytes for sodium-ion batteries.
[0003] In sodium-ion batteries, iron-based polyanion cathode materials have attracted extensive attention due to their low price, environmental friendliness, excellent cycle performance and good safety. In recent years, sodium iron pyrophosphate has been confirmed as an electrochemically active cathode material. 4 Fe 3 (PO 4 ) 2 P 2 O 7 and Na 3 Fe 2 (PO 4 ) 2 O 7 The theoretical capacity of the positive electrode is 128 mAh / g and 119 mAh / g respectively, which has great application prospects. 4 Fe 3 (PO 4 ) 2 P 2 O 7 , it has high initial capacity, low raw material cost and good cycle performance, and is suitable for large-scale energy storage systems.
[0004] Based on cost considerations, the raw materials for the industrial production of sodium iron pyrophosphate are mainly sodium carbonate, iron phosphate, and sodium dihydrogen phosphate. The preparation method is to add the sodium source, iron source, phosphorus source, carbon source, and complexing agent into a solvent, mix them evenly, and then dry them to obtain a precursor; then the precursor is pre-sintered and sintered in a protective atmosphere to obtain the sodium iron pyrophosphate positive electrode material. However, due to the presence of impurities NaFePO 4 , resulting in poor performance of the positive electrode material, and sodium carbonate is easily decomposed into gas during ball milling mixing, which is highly dangerous. Summary of the invention
[0005] Based on the above technical problems existing in the prior art, the present invention provides a method for preparing a pure-phase sodium ion battery positive electrode material, which can obtain pure-phase sodium iron phosphate pyrophosphate by mixing sodium carbonate and a specific carbon source for reaction and combining a specific mixing step.
[0006] In order to achieve the above object, the technical solution of the present invention is as follows:
[0007] A method for preparing a pure phase sodium ion battery positive electrode material, wherein the positive electrode material is a carbon-coated sodium iron phosphate pyrophosphate material, and the chemical formula of the sodium iron phosphate pyrophosphate is: Na a Fe b (PO 4 ) c P 2 O 7 , wherein 3≤a≤4, 2≤b≤4, 1≤c≤3; and the preparation method thereof comprises the following steps:
[0008] S1. Weigh sodium carbonate, ferric phosphate, sodium dihydrogen phosphate, citric acid and dispersant according to the stoichiometric ratio;
[0009] S2, first dissolving sodium carbonate and citric acid in a solvent to react to obtain a first slurry;
[0010] S3, combining the first slurry, iron phosphate, sodium dihydrogen phosphate and a dispersant to obtain a second slurry;
[0011] S4, drying the second slurry to obtain a precursor;
[0012] S5, pre-sintering the precursor in a protective gas atmosphere, and then continuing to heat up for sintering to obtain the positive electrode material.
[0013] In some embodiments, in step S2, citric acid is first dissolved in a solvent, and then sodium carbonate is added to the citric acid solution in batches within 10-30 minutes to react.
[0014] In some embodiments, in step S3, the first slurry, iron phosphate, sodium dihydrogen phosphate and a dispersant are mixed and ball-milled, and the ball-to-material ratio is 10-20: 1. Preferably, the solid content of the slurry obtained after mixing is 40%-60%.
[0015] In some embodiments, the ball milling rate is 400-800 rpm; and the ball milling time is 8-24 h.
[0016] In some embodiments, in step S5, the pre-sintering temperature is 300-450°C; and the sintering temperature is 500-800°C.
[0017] In some embodiments, the pre-sintering time is 3-8 hours; and the sintering time is 8-24 hours.
[0018] In some embodiments, the heating rates to the pre-sintering temperature and the sintering temperature are both 1-10° C. / min; preferably, the heating rates are both 2-5° C. / min.
[0019] In some embodiments, the dispersant is at least one of polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol.
[0020] In some embodiments, in step S1, raw materials are weighed so that the molar ratio of Na:Fe:P is 4:3:4 and the mass ratio of citric acid to dispersant is 2-4:1.
[0021] In some embodiments, the solvent is an alcohol solvent; preferably, ethylene glycol.
[0022] In some embodiments, in step S4, vacuum drying is performed at 70-100°C.
[0023] In some embodiments, the method further comprises passing the dried material through a 250-500 mesh sieve.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention uses sodium carbonate, iron phosphate, and sodium dihydrogen phosphate as the sodium source, iron source, and phosphorus source, respectively, and citric acid as the carbon source. Sodium carbonate and citric acid are first mixed for reaction, then mixed with other raw materials, dried to obtain a precursor, and then pre-sintered and sintered to obtain pure phase sodium ferric phosphate pyrophosphate. The scheme of the present invention, by strictly controlling the step of mixing raw materials, first mixing sodium carbonate and citric acid for reaction and then mixing with other raw materials for subsequent steps, can effectively solve the problem of poor material performance caused by the presence of impurities in the traditional process for preparing sodium ferric phosphate pyrophosphate, so that the obtained sodium ferric phosphate pyrophosphate positive electrode material is pure phase, its specific capacity is closer to the theoretical specific capacity, and has good cycle stability; the use of dispersant in the present invention can not only limit the growth of precursor particles, but also as a new carbon source introduced, further improve the conductivity of the positive electrode material, and then improve the electrochemical performance of the positive electrode material.
[0026] In addition, the raw material source of the present invention is abundant and low in price, and it can be used for industrial production of sodium iron pyrophosphate positive electrode material, which can effectively improve the utilization rate of raw materials and reduce production costs; and because sodium carbonate and citric acid are reacted first, it can be avoided that sodium carbonate generates gas in the subsequent reaction process, which makes the subsequent reaction process dangerous. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The Na obtained in Example 1 4 Fe 3 (PO 4 ) 2 P 2 O 7 / SEM image of C positive electrode material;
[0028] Figure 2The Na obtained in Example 1 4 Fe 3 (PO 4 ) 2 P 2 O 7 / XRD pattern of C positive electrode material;
[0029] Figure 3 The Na obtained in Example 1 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C charge and discharge specific capacity diagram of positive electrode material;
[0030] Figure 4 The Na obtained in Example 1 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C positive electrode material cycle performance diagram of 200 cycles under 0.5C conditions. DETAILED DESCRIPTION
[0031] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0033] Example 1
[0034] A pure phase sodium ion battery cathode material Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C preparation method, comprising the following steps:
[0035] S1: weigh the raw materials according to the stoichiometric ratio: 8 g sodium carbonate, 22.85 g iron phosphate, 6.05 g sodium dihydrogen phosphate, 30 g citric acid, and 10 g polyvinyl alcohol;
[0036] S2: First, dissolve citric acid in 20 ml of ethylene glycol and stir, then slowly add sodium carbonate (add in batches within 10 min), ultrasonically disperse for 10 min, and stir at 600 rpm for 3 h to obtain slurry 1;
[0037] S3: Dissolve iron phosphate and sodium dihydrogen phosphate in 50 ml of ethylene glycol and stir, disperse by ultrasonic for 10 min, and stir at 500 rpm for 5 h to obtain slurry 2;
[0038] S3: Slurry 1, slurry 2 and dispersant were added to a ball mill with a ball-to-material ratio of 10:1 and a solid-liquid ratio of 45%, and ball milled at a speed of 800 rpm for 12 h;
[0039] S4: placing the ball-milled slurry in a vacuum oven at 80°C for 12 hours;
[0040] S5: Sieve the dried material through a 400-mesh sieve, take the material under the sieve, and obtain a precursor;
[0041] S6: Place the precursor in a tube furnace, and in a nitrogen atmosphere, first heat it to 300°C and keep it for 5 hours; then heat it to 530°C and keep it for 10 hours, during which the heating rate is always 3°C / min, to obtain Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C material.
[0042] The obtained materials were characterized by SEM and XRD, and the characterization results were as follows: Figure 1 and Figure 2 shown.
[0043] like Figure 2 , the Na obtained in this embodiment 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C materials and Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 The standard card is completely overlapped and there is no impurity peak, indicating that the material prepared in this example is a pure phase material.
[0044] The obtained materials were subjected to electrochemical performance tests, as follows:
[0045] The material prepared in this example was 4 Fe 3 (PO4 ) 2 P 2 O 7 / C: conductive carbon black: binder in a mass ratio of 7:2:1 to prepare a positive electrode slurry, and then apply it on an aluminum foil by a doctor blade coating method; the aluminum foil coated with the positive electrode slurry is placed in an oven, dried at 80°C for 8h, and then cut into discs; a metal sodium sheet is used as a counter electrode, a glass fiber is used as a separator, and a 1 mol / L sodium perchlorate solution of ethylene carbonate (EC) and diethyl carbonate (DEC) is used as an electrolyte (the volume ratio of EC and DEC is 1:1), and button cells are assembled in a glove box; the electrochemical performance of the assembled button cells is tested, and the test results are shown in FIG. Figure 3 and Figure 4 shown.
[0046] like Figure 3 , the Na obtained in this embodiment 4 Fe 3 (PO 4 ) 2 P 2 O 7 The discharge specific capacity of the / C material at a current density of 0.5C is 109.5mAh / g.
[0047] like Figure 4 , the Na obtained in this embodiment 4 Fe 3 (PO 4 ) 2 P 2 O 7 After 200 charge and discharge cycles at a current density of 0.5C, the capacity retention rate of the / C material is 95%.
[0048] Example 2
[0049] A pure phase sodium ion battery cathode material Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C preparation method, comprising the following steps:
[0050] S1: weigh the raw materials according to the stoichiometric ratio: 8 g sodium carbonate, 22.85 g iron phosphate, 6.05 g sodium dihydrogen phosphate, 30 g citric acid, and 10 g polyvinyl alcohol;
[0051] S2: First, dissolve citric acid in 20 ml of ethylene glycol and stir, then slowly add sodium carbonate (add in batches within 10 min), ultrasonically disperse for 10 min, and stir at 600 rpm for 3 h to obtain slurry 1;
[0052] S3: Dissolve iron phosphate and sodium dihydrogen phosphate in 50 ml of ethylene glycol and stir, disperse by ultrasonic for 10 min, and stir at 500 rpm for 5 h to obtain slurry 2;
[0053] S3: Slurry 1, slurry 2 and dispersant were added to a ball mill with a ball-to-material ratio of 10:1 and a solid-liquid ratio of 45%, and ball milled at a speed of 800 rpm for 12 h;
[0054] S4: placing the ball-milled slurry in a vacuum oven at 80°C for 12 hours;
[0055] S5: Sieve the dried material through a 400-mesh sieve, take the material under the sieve, and obtain a precursor;
[0056] S6: Place the precursor in a tube furnace, and heat it to 300°C in a nitrogen atmosphere, and keep it for 5 hours; then heat it to 550°C, and keep it for 10 hours. During this period, the heating rate is always 3°C / min, and Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C material.
[0057] After testing, the Na obtained in this embodiment 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C material, the discharge specific capacity at a current density of 0.5C is 110mAh / g; after 200 charge and discharge cycles at a current density of 0.5C, the capacity retention rate is 96%.
[0058] Comparative Example 1
[0059] A sodium ion battery positive electrode material Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C preparation method, comprising the following steps:
[0060] S1: weigh the raw materials according to the stoichiometric ratio: 8 g sodium carbonate, 22.85 g iron phosphate, 6.05 g sodium dihydrogen phosphate, 30 g citric acid, and 10 g polyvinyl alcohol;
[0061] S2: Sodium carbonate, iron phosphate, sodium dihydrogen phosphate, citrate and polyvinyl alcohol were added to 70 ml of ethylene glycol and stirred at 500 rpm for 5 h to obtain a slurry;
[0062] S3: Add the obtained slurry into a ball mill with a ball-to-material ratio of 10:1 and a solid-liquid ratio of 45%, and mill at a speed of 800 rpm for 12 h;
[0063] S4: placing the ball-milled slurry in a vacuum oven at 80°C for 12 hours;
[0064] S5: Sieve the dried material through a 400-mesh sieve, take the material under the sieve, and obtain a precursor;
[0065] S6: Place the precursor in a tube furnace, and in a nitrogen atmosphere, first heat it to 300°C and keep it for 5 hours; then heat it to 530°C and keep it for 10 hours, during which the heating rate is always 3°C / min, to obtain Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C material.
[0066] After testing, the Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 / C material, the discharge specific capacity at a current density of 0.5C is 106mAh / g; after 200 charge and discharge cycles at a current density of 0.5C, the capacity retention rate is 89%.
[0067] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0068] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a pure phase sodium ion battery positive electrode material, characterized in that: The positive electrode material is a carbon-coated sodium iron phosphate pyrophosphate material, and the chemical formula of the sodium iron phosphate pyrophosphate is: Na a Fe b (PO4) c P2O7, wherein 3≤a≤4, 2≤b≤4, 1≤c≤3; and the preparation method thereof comprises the following steps: S1. Weigh sodium carbonate, ferric phosphate, sodium dihydrogen phosphate, citric acid and dispersant according to the stoichiometric ratio; S2, first dissolving sodium carbonate and citric acid in a solvent to react to obtain a first slurry; S3, mixing the first slurry, iron phosphate, sodium dihydrogen phosphate and a dispersant to obtain a second slurry; S4, drying the second slurry to obtain a precursor; S5, pre-sintering the precursor in a protective gas atmosphere, and then continuing to heat up for sintering to obtain the positive electrode material.
2. The method for preparing a pure phase sodium ion battery positive electrode material according to claim 1, characterized in that: In step S2, citric acid is first dissolved in a solvent, and then sodium carbonate is added to the citric acid solution in batches within 10-30 minutes to react.
3. The method for preparing a pure phase sodium ion battery positive electrode material according to claim 1, characterized in that: In step S3, the first slurry, iron phosphate, sodium dihydrogen phosphate and a dispersant are mixed and ball-milled, with a ball-to-material ratio of 10-20:
1.
4. The method for preparing a pure phase sodium ion battery positive electrode material according to claim 3, characterized in that: The ball milling speed was 400-800 rpm.
5. The method for preparing a pure phase sodium ion battery positive electrode material according to claim 1, characterized in that: In step S5, the pre-sintering temperature is 300-450°C; and the sintering temperature is 500-800°C.
6. The method for preparing a pure phase sodium ion battery positive electrode material according to claim 5, characterized in that: The heating rates of pre-sintering and sintering are both 1-10°C / min.
7. The method for preparing a pure phase sodium ion battery positive electrode material according to claim 1, characterized in that: The dispersant is at least one of polyvinyl pyrrolidone, polyethylene glycol and polyvinyl alcohol.
8. The method for preparing a pure phase sodium ion battery positive electrode material according to claim 1, characterized in that: The solvent is an alcohol solvent.
9. The method for preparing a pure phase sodium ion battery positive electrode material according to claim 1, characterized in that: In step S1, raw materials are weighed according to the molar ratio of Na:Fe:P being 4:3:4 and the mass ratio of citric acid to dispersant being 2-4:
1.
10. The positive electrode material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Iron-based composite phosphate positive electrode material, preparation method thereof, positive plate and sodium ion battery
CN114597385A
Preparation method and application of ferric sodium pyrophosphate material
CN117393751A
Microwave assisted sol-gel process for preparing in-situ carbon coated electrode materials and the product there of
IN201911008004A
Cited By
Preparation method and application of carbon shell coated ferric sodium pyrophosphate positive electrode material adaptive to aqueous binder
CN121020537A